Implementasi Pencatatan Keuangan Sederhana dan Digitalisasi Pemasaran Digital pada UMKM Laundry di Dusun Gatak - Al Nufus, Hafiz; Paramitalaksmi, Ratri (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The mentoring program was implemented to address issues related to the low practice of financial recordkeeping and the suboptimal utilization of digital marketing among Aisyah Laundry MSMEs in Dusun Gatak. The objective of this activity was to implement a simple financial recording system, build a basic understanding of the separation between personal and business finances, and introduce digital marketing strategies aimed at enhancing business management effectiveness. The methods employed included a participatory approach through initial condition observation, socialization of the benefits of recordkeeping, training in the use of simple bookkeeping formats, digital content training, and outcome evaluation. The results demonstrated a significant improvement in the regularity of daily transaction recording, administrative skills, and the establishment of a more systematic financial management pattern. In the marketing aspect, activation of the business’s Instagram account contributed to expanded service information outreach, increased customer interest, and a shift in the business owner's perspective regarding the importance of digital media. These findings affirm that hands-on mentoring is effective in improving financial and digital literacy among MSMEs and in encouraging sustainable changes in business behavior.